Advective relief of CO 2 limitation in microphytobenthos in highly productive sandy sediments - Perran L. M. Cook; Hans Røy (Limnology and Oceanography, 2006)
Following field observations of increased photosynthesis at increased rates of sediment flushing in sandy sediments, we conducted a series of laboratory experiments to elucidate the mechanism behind these observations. Column experiments in which water was pumped though sand at rates ranging from 0 to 613 L m −2 d −1 showed that carbon (C) fixation, as measured using carbon‐14 ( 14 C) incorporation, increased from 6.4 to 8.6 mmol m −2 h −1 with increasing rates of flushing. Bottle incubations showed that the addition of inorganic nutrients [ammonium ion (NH 4 + ), inorganic phosphate (HPO 4 − ), silicic acid Si(OH) 4 ] did not stimulate C fixation over short‐term incubations. Microprofiles of pH showed that the pH within the photic zone increased to 8.9, reducing free carbon dioxide (CO 2 ) concentrations to ~0.5 µmol L −1 . Further bottle incubations, where pH and total inorganic carbon (TCO 2 ) were manipulated, showed that high pH (9.6) did not affect photosynthesis if free CO 2 was present at concentrations of 10 µmol L −1 , suggesting a direct effect of low free CO 2 concentrations. 14 C fixation profiles at a resolution of 100 µm recorded by b‐radiation imaging showed that while the depth specific maximum rates of C fixation were the same under both diffusive and advective (flushed) conditions, the integrated rates of photosynthesis were highest under flushed conditions because of a thickening of the photosynthetic zone. We conclude that advective pore‐water transport can enhance benthic photosynthesis in shallow permeable sand sediments by counteracting CO 2 limitation.